Nutritional support of the critically Ill pediatric patient: foundations and controversies (2017)
Critically ill children require nutritional support that will give them nutritional and non-nutritional support to successfully deal with their disease. In the past few years, we have been able to better understand the pathophysiology of critical illness, which has made possible the establishment of nutritional strategies resulting in an improved nutritional status, thus optimizing the pediatric intensive care unit (PICU) stay and decreasing morbidity and mortality. Critical illness is associated with significant metabolic stress. It is crucial to understand the physiological response to stress to create nutritional recommendations for critically ill pediatric patients in the PICU.